Physiotherapy management of Triangular Fibrocartilage Complex (TFCC) : Case Study - Faizah, Zulfa Nur; Fatmarizka, Tiara; Abdurrasyid, Abdurrasyid (FISIO MU: Physiotherapy Evidences, 2023)
Martial arts is a sport that is enjoyed by many people, both men and women. According to the researchers' initial observations, these martial arts groups began to emerge. . Muay Thai is a martial art that uses kicks, punches and slams, and is more dominant in the form of free combat martial arts that first came from Thailand. Observations made by researchers at Medan Muay Thai Gajah Mada found that they experienced shortness of breath and fatigue, 30% had ankle injuries, another 20%. Minor injuries to TFCC can be classified as sprains of the wrist. As the name implies, the soft tissue of the wrist is complex. Disturbance to the area from injury or degeneration can result in more serious impairment of a wrist sprain, such as disability. pain occurs throughout the wrist area. The pain is aggravated by any activity or position that requires rotation of the forearm and movement toward the ulna. These movements are simple activities such as turning a doorknob or a lock. This study used physiotherapy interventions in the form of ice packs to reduce swelling and pain, then exercise therapy to improve wrist stability, ultrasound and also TENS to stimulate the surrounding muscles. Evaluation of the results aims to assess the reduction in swelling and pain and how much the stability of the wrist has increased postoperatively.